Inflation and economic growth nexus in South Africa before implementation of national development plan: Is there an optimal inflation threshold? - Tshuma, Mthokozisi; Ndou, Eliphas (Asian Journal of Empirical Research, 2025)
This study estimates a logistic smooth transition regression model to determine the optimal inflation threshold in the nonlinear relationship between inflation and economic growth in South Africa. The analysis, using quarterly data from 1975 to 2011, predates the 2012 launch of the National Development Plan and more than a decade of slow economic growth. The aim is to identify the optimal inflation threshold level that either supports or hinders growth. The findings indicate an optimal inflation threshold of 3%. Inflation below this level significantly enhances economic growth, while surpassing it noticeably reduces economic progress and raises concerns about price challenges. These results suggest that the negative effects of rising inflation intensify beyond a 3% increase. This research contributes to South Africa’s ongoing debate on adjusting the inflation target by modeling the nonlinear inflation-growth relationship via a logistic smooth transition regression method. Overall, the policy implication drawn from this study is that maintaining inflation below the optimal inflation threshold level in South Africa is essential, as it promotes economic growth. The findings support the South African Reserve Bank’s aim to lower its inflation target to 3%, indicating potential economic benefits from such a reduction.